Le disposizioni alla stampa del Ministero della Cultura popolare (Minculpop): Considerazioni linguistiche e analisi storica - Benatti, Ruben; Rosselli, Alessandro (Études sur la Région Méditerranéenne, 2021)
The study considers, from a linguistic and historical point of view, a problem disrgegarded until today by the Italian historiography: the case of veline, the orders for the press sent during the Fascist dictatorship from the Ministero della Cultura Popolare (Popular Culture Ministry) to all Italian newspapers, deciding on news that may or may not be published and prohibiting the publication of materials potentially dangerous for the Fascist regime. The study is founded on an anthology published in Italy in 2005, containing a selection of veline from 1932 to 1943, and consist in two parts: the first concerning some linguistic features (especially lexical features) and the second concerning a historical analysis. This is meant to be a prompt for wider research on his topic, both on the linguistic and historical side.